Revisiting the Barriers to and Facilitators of Research Utilization in Nursing: A Systematic Review - Tuppal, Cyruz P; Vega, Paolo D; Ninobla, Marina Magnolia G.; Al-Battashi, Abdullah; Arquiza, Glenda; Baua, Elizabeth P; ReÃ±osa, Mark Donald (Nurse Media Journal of Nursing, 2019)
Background: Nursing profession continues to evolve, expand, and link its practice that requires evidence to strengthen its body of knowledge, and research utilization (RU) is pivotal towards this realization.Purpose: This systematic review aimed to critically identify, select, appraise, and synthesize research evidence about the barriers to and facilitators of research utilization.Methods: There were 17,961 papers during the initial database search and 85 papers from other sources from the electronic databases including Web of Science, CINAHL, Complete, Scopus, OVID, Medline, PsychInfo, SocIndex, Internurse, British Nursing Index, ERIC, and PubMed. After further analysis, thirty-six articles were included in the analysis that explicitly identified and described the barriers to and facilitators of research utilization in nursing.Results: Based on the findings, the lack of awareness about research, lack of authority to change their practice, overwhelming publications, and lack of compiled literature were the topmost identified barriers to RU. On the other hand, organizational and colleague support, and continuing education as both personal and professional commitment can further facilitate research utilization.Conclusion: Despite extensive studies conducted addressing the barriers to research utilization, the findings suggest a consistent reproach on the capability of nurses to maximize and utilize research. The same elements that may serve as barriers to, can likewise become the impetus in gaining sufficient research utilization among nurses.